Sudden Influxes of Resource Wealth to the Economy : Avoiding 'Dutch Disease' - Mendez Ramos, Fabian (World Bank, Washington, DC, 2020)
Dutch Disease is a condition in which a sudden increase of resource wealth from an extractive sector (such as oil, gas, coal, or mining) undermines other areas of the economy (such as agriculture, manufacturing, or tradeable services), shrinking them while spurring an appreciation in the real exchange rate. Although this may have some positive effects in the short run, Dutch Disease episodes can potentially lead to sectoral concentration and lower economic growth in the long run. This policy brief takes a systematic look at this macroeconomic phenomenon, collects evidence for 83 countries from 1998 to 2017, and summarizes policies that aim to prevent or mitigate Dutch Disease and some of its effects. A long-term perspective to prevent excessive dependence on natural resources and promote broad-based growth should include improvements in institutional governance of natural resource wealth, development of the financial sector to provide risk management products, and diversification of the economy through selective taxes and provision of public goods.